Apatite Thermochemistry: the Simple Salt Approximation - Glasser, Leslie (American Chemical Society, 2019)
Drouet has recently comprehensively reviewed the thermochemistry of phosphate apatites, M10(PO4)6X2. On the basis of the data assembled, he has established an optimized additive set of data values based upon the component ions, M2+, P2O5, or PO43–, and halide or OH– ions, which yield phosphoapatite enthalpy and Gibbs energy values generally within 1% of their experimental values. In this paper, we introduce and compare the Simple Salt Approximation (SSA) for generation of the same thermodynamic values by addition of values for the component salts of the apatite. SSA is widely applicable to ionic systems so that familiarity with this procedure is worthwhile. Drouet’s additive values focused on phosphoapatites yield better results (at 1%) than does the more general SSA (at ∼3%), but the SSA provides an alternative to data prediction when the Drouet additive factors are not available. In addition, we here use the SSA to generate approximate entropy values and estimate the Debye temperature of phosphoapatites under ambient conditions, yielding insight into the extent of activation of their vibrational modes.